PENGARUH LITERASI KEUANGAN TERHADAP PENGELOLAAN KEUANGAN UMKM DI TORAJA UTARA - Palimbong, Stefani; Pompeng, Olivia Devi Yulian (Jurnal Unicorn ADPERTISI, 2022)
This study aims to determine the influence of financial literacy on the financial management of MSMEs in North Toraja. This type of research uses quantitative methods with a descriptive type of research. Sampling was carried out using the Pursosive Sampling method, with a total population of 147 with a total of 60 respondents studied. The data collection technique in this study is the distribution of questionnaires by collecting answers from respondents through statements or questions. The data analysis techniques used in this study are simple linear regression analysis, validity test, reliability test, and hypothesis test. The results showed that financial literacy has a positive and significant effect on the financial management of MSMEs in North Toraja.